DAMPAK PEMEKARAN DESA TERHADAP PEMBANGUNAN INFRASTRUKTUR DI DESA KAPU JAYA KECAMATAN PALANGGA KABUPATEN KONAWE SELATAN - Mudana, Made; Nempung, Tibertius; Millia, Heppi (JURNAL EKONOMI UHO, 2016)
This study aims to evaluate  the impact of  regional expansion on  infrastructure development in Kapu Jaya Village. The primary data obtained through interviews of head of village,  and  questionare to 60 respondent. The analytical method  is  used descriptive analysis.  The results showed that regional expansion in Kapu Jaya Village have  positive impact in infrastructure development.  About 80 percent respondent  assume  that   regional expansion  improve  availability in roads and infrastructure,   health care facilities,  medical personnel,  medicines, and education.